2020
DOI: 10.1002/mats.201900051
|View full text |Cite
|
Sign up to set email alerts
|

Energy Renormalization for Coarse‐Graining Polymers with Different Fragilities: Predictions from the Generalized Entropy Theory

Abstract: Bottom‐up prediction of physical performance of glass‐forming (GF) polymers via coarse‐grained (CG) modeling is challenging because these CG models normally experience significantly altered dynamics that strongly vary with temperature. Building upon the recently developed energy‐renormalization (ER) coarse‐graining method based on molecular dynamics simulations, generalized entropy theory (GET) is employed to theoretically investigate the influence of fundamental molecular parameters on CG modeling of polymers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…To complement our simulation results, we perform calculations based on the GET . Details regarding the calculations of the structural relaxation time and characteristic temperatures of glass formation can be found elsewhere, e.g., in refs and . Notably, following AG, the GET neglects the entropy Δ S o of activation in estimating the activation free energy, an approximation that needs to be avoided in future work aimed at improving the quantitative predictive power of the GET.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To complement our simulation results, we perform calculations based on the GET . Details regarding the calculations of the structural relaxation time and characteristic temperatures of glass formation can be found elsewhere, e.g., in refs and . Notably, following AG, the GET neglects the entropy Δ S o of activation in estimating the activation free energy, an approximation that needs to be avoided in future work aimed at improving the quantitative predictive power of the GET.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Finally, let us comment on the experimental observation that the activation volume can sometimes increase rather than decrease with increasing temperature. This opposite trend is natural in macroscopic crystalline or semi-crystalline materials, in which collective motion often increases upon heating rather than upon cooling, or sometimes even varies nonmonotonically with temperature in superheated crystalline materials, a prevalent phenomenon in ionic and crystalline materials and probably many materials composed of polar molecules. Tellingly, the temperature dependence of the activation volume in semi-crystalline materials of engineering interest has been observed to invert at low temperatures when the crystalline grains have a nanoscale size, a phenomenon that can be understood by relaxation dominated by grain boundary diffusion in nanocrystalline materials. , This situation is natural since the dynamics within the grain boundaries, , or more broadly, the interfacial dynamics of crystalline materials , and nanoparticles, is similar in many ways to that of glass-forming liquids; in particular, the interfacial dynamics is dominated by the stringlike collective motion that either grows or decreases upon cooling, depending on the particular conditions interfacial regions involved .…”
Section: Discussionmentioning
confidence: 99%
“…The LCT has also been extended to model polymers with specific interactions , where cohesive interaction strengths are different between united-atom groups and telechelic polymers where associative groups at the chain ends have strong interactions, enabling predictions of glass formation in these polymer systems when combined with the AG model . It is also worth mentioning that the GET has been shown to be useful for coarse-grained modeling of polymeric GF materials. , Thus, the GET has the unique capacity to investigate the influence of structural details and interactions on polymer glass formation and better understand a variety of important problems in polymer glass formation.…”
Section: Generalized Entropy Theory (Get) Of Polymer Glass Formationmentioning
confidence: 99%
“…18 It is also worth mentioning that the GET has been shown to be useful for coarse-grained modeling of polymeric GF materials. 183,184 Thus, the GET has the unique capacity to investigate the influence of structural details and interactions on polymer glass formation and better understand a variety of important problems in polymer glass formation.…”
Section: Generalized Entropy Theory (Get) Ofmentioning
confidence: 99%
“…There is also a need for better quantification of packing frustration in terms of metrics that are experimentally accessible, given the significance of this property for film dynamics. Xu et al 92 have suggested based on recent calculations based on the generalized entropy theory, that the thermal expansion coefficient and isothermal compressibility should provide useful practical metrics for quantifying packing frustration in measurement and simulation. For example, recent findings have indicated that packing frustration can be related to the thermal expansion coefficient or the isothermal compressibility in bulk materials, 93 and we should seek useful analogs of these properties in thin films.…”
Section: ■ Conclusionmentioning
confidence: 99%